2009
DOI: 10.1186/1471-2474-10-151
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound evidence of altered lumbar connective tissue structure in human subjects with chronic low back pain

Abstract: BackgroundAlthough the connective tissues forming the fascial planes of the back have been hypothesized to play a role in the pathogenesis of chronic low back pain (LBP), there have been no previous studies quantitatively evaluating connective tissue structure in this condition. The goal of this study was to perform an ultrasound-based comparison of perimuscular connective tissue structure in the lumbar region in a group of human subjects with chronic or recurrent LBP for more than 12 months, compared with a g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
167
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 177 publications
(178 citation statements)
references
References 36 publications
(23 reference statements)
7
167
1
2
Order By: Relevance
“…1,38,54 With respect to the abdominal connective tissue, no studies could be identified that assessed changes in these tissues in persons with LPP. However, Langevin et al, 31 using ultrasound imaging (USI), reported the presence of thicker and more disorganized lumbar perimuscular connective tissue (PMCT) at the L2-3 vertebral level in individuals with longstanding low back pain (LBP).…”
Section: T T Resultsmentioning
confidence: 99%
“…1,38,54 With respect to the abdominal connective tissue, no studies could be identified that assessed changes in these tissues in persons with LPP. However, Langevin et al, 31 using ultrasound imaging (USI), reported the presence of thicker and more disorganized lumbar perimuscular connective tissue (PMCT) at the L2-3 vertebral level in individuals with longstanding low back pain (LBP).…”
Section: T T Resultsmentioning
confidence: 99%
“…44 To date, the most common use of USI in studies by physical therapists has been measurement of the architectural characteristics of muscle, which usually involves measuring parameters such as thickness, 59,60,65 width, 8,65 and cross-sectional area (CSA), 8,43,65 and comparing changes or differences in these parameters between groups of individuals 19,70 or over time-before and after some event (eg, injury) 8 or intervention (eg, training).…”
Section: What Information Does Conventional Grayscale Ultrasound Imagmentioning
confidence: 99%
“…22,23 As a decrease in muscle size has been linked to various pathologies and impairments, 16,19 the use of the technology has continued to expand to include investigation of muscles such as the supraspinatus and infraspinatus, 35 rectus femoris, 13 biceps brachii, 2 transversus abdominis (TrA) and internal oblique (IO), 20 rectus abdominis, 8 cervical multifidus, 45 trapezius, 56 rectus femoris, sartorius, and iliopsoas. 53 Other aspects of muscle morphology and function that have been explored with USI include composition, 44,61,66 changes in internal architecture (pennation angles), 48,80 force generation, 13 and muscle activity (ie, electrical activity recorded by electromyography [EMG]). 6,28,34,36,52 While physical therapists are familiar with therapeutic ultrasound and the underlying physics, they often lack training regarding the principles and instrumentation underlying USI.…”
Section: T T Synopsismentioning
confidence: 99%
“…[1] Episakral lipoma, torakodorsal fasyadaki bir yırtık sonucu fıtıklaşmış subfasiyal yağ dokusudur. Çeşitli çalışmalar ile episakral lipomanın akut ve kronik bel ağrısının önemli nedenlerinden biri olduğu ve ciddi bel ağrısına ve sakatlanmaya yol açabileceği gösteril-miştir.…”
Section: Introductionunclassified